Knowledge and practice of galactogogeus consumption among breastfeeding mothers in Kuantan, Pahang - Abdul Rahim, Nurshuhaida; Abdul Ghani, Radiah; A. Rahman, Nor Azlina (2014)
It is well recognize that breast milk give many benefits to the infants. The best nutrition for early months of growth for normal infants is exclusive breastfeeding as suggested by Canadian Pediatric Society (CPS). Almost all reasons that have been documented for discontinuance of breast milk are perception of insufficient production of milk. In order to increase the amount of milk, many breastfeeding mothers take an effort to take supplement, known as galactogogues which been claimed to increase quality and quantity of breast milk. However, the exact effect of galactogogues is still questionable. Therefore, this study aims to investigate the effect of galactogogues consumption on milk production among breastfeeding mothers in Kuantan. Besides that, this study also aims to identify the most preferred type of galactogogues consumption among mothers in Kuantan, Pahang. Apart from that, it was conducted to find out the association between knowledge and practice of galactogogues consumption among breastfeeding mothers in Kuantan. This is a cross-sectional study and 120 respondents were selected by using purposive sampling. The questionnaire forms were distributed among mothers who fit the inclusion criteria in Kuantan area. According to our findings, about 74% of subjects responded that galactogogues can enhanced milk production of breastfeeding mothers while 38% responded that galactogogues does not give any effect. The most preferred type of galactogogues among mothers in Kuantan is food (57%) compared to herb (34%) and drug (8%). Apart from that, there are association between knowledge and practice of galactogogues consumption among breastfeeding mothers in Kuantan. In conclusion, knowledge of galactogogues consumption among breastfeeding mothers in Kuantan was good and the practice was prevalent among them.